The erotetic theory of attention: questions, focus, and distraction - Koralus, P (Wiley-Blackwell, 2014)
Attention has a role in much of perception, thought, and action. On the erotetic theory, the functional role of attention is a matter of the relationship between questions and what counts as answers to those questions. Questions encode the completion conditions of tasks for cognitive control purposes, and degrees of attention are degrees of sensitivity to the occurrence of answers. Questions and answers are representational contents given precise characterizations using tools from formal semantics, though attention does not depend on language. The erotetic theory proposes an integrated account of attention in cognitive control and of attentional focus in perception. The functional role of attentional focus on objects, properties, and locations has to do with picking out something that corresponds to what a task is ‘about’. The erotetic theory of attention opens new avenues in theorizing about the relationship between attention, representational content, phenomenal character, and practical reason. A novel representationalist account of salience is proposed. The theory also provides an account of distraction that suggests when distraction is a defect in practical reasoning.